2018
DOI: 10.3389/fimmu.2018.00586
|View full text |Cite
|
Sign up to set email alerts
|

Age and Age-Related Diseases: Role of Inflammation Triggers and Cytokines

Abstract: Cytokine dysregulation is believed to play a key role in the remodeling of the immune system at older age, with evidence pointing to an inability to fine-control systemic inflammation, which seems to be a marker of unsuccessful aging. This reshaping of cytokine expression pattern, with a progressive tendency toward a pro-inflammatory phenotype has been called “inflamm-aging.” Despite research there is no clear understanding about the causes of “inflamm-aging” that underpin most major age-related diseases, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
719
2
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 932 publications
(769 citation statements)
references
References 471 publications
(435 reference statements)
25
719
2
23
Order By: Relevance
“…1). A number of studies have reported that aging decreases mRNA expressions of nerve growth factor, nitric oxide synthase, and long-term potentiation-related genes, and increases the expression of genes associated with NADPH oxidase and inflammation [26][27][28][29][30]. Our result demonstrated that mRNA expression levels of Gp91 phox and Mcp-1 were elevated with aging, while Ampa1 expression levels significantly declined (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…1). A number of studies have reported that aging decreases mRNA expressions of nerve growth factor, nitric oxide synthase, and long-term potentiation-related genes, and increases the expression of genes associated with NADPH oxidase and inflammation [26][27][28][29][30]. Our result demonstrated that mRNA expression levels of Gp91 phox and Mcp-1 were elevated with aging, while Ampa1 expression levels significantly declined (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…2 Not surprisingly, a progressive propensity toward a proinflammatory phenotype, identified as inflamm-aging, plays a key role in the remodeling of the immune system at older ages, with evidence pointing to an inability to fine-control inflammation. 5 Thus, in our opinion, the role of the thymus could be crucial in the modulation of the immune response toward SARS-CoV-2 leading to a less severe phenotype in children when compared with those in adult COVID-19 patients. On the other hand, inflamm-aging associated with the absence of thymopoietic mechanisms could be a predisposing condition that sustains the cytokine release storm as is most often reported in adult COVID-19 subjects, especially in the older COVID-19 patients.…”
Section: Dear Editormentioning
confidence: 85%
“…Aging is one of the major risk factors for MI, and monocytederived cardiac macrophages as well as granulocytes increase in numbers during aging while the overall macrophage population decreases (Molawi et al, 2014). Aging is also related to clonal hematopoiesis with a myeloid bias, an overall increased systemic inflammatory tone, dysregulation of soluble mediators including cytokines, chemokines, and growth factors all together reducing immune tolerance, a phenotype also described as ''inflamm-aging'' (Fuster et al, 2017;Jaiswal et al, 2017;Rea et al, 2018;Swirski, 2018). However, the overall impact of these age-related changes within the hematopoietic and the immune system on the onset of MI have not been quantified to detail yet and certainly need further clarification.…”
Section: Myelopoiesis In Context Of Acute and Chronic Inflammationmentioning
confidence: 99%